PSIKOLOGI POSTMODERNISME: Kritik dan Tawaran terhadap Psikologi Positivistik - Arman Marwing (IAIN Tulungagung, 2017)
Positivistic hegemony in psychology is entrenched from the beginning of its birth in 1879. The ontology of modern psychology emphasizes on observable empirical realities. However, the human side of the aspect of the imaginable region is included in irrationality. This work system is seen in the process of diagnostic classification of mental disorders in PPDGJ which is full of cultural bias or legal practice of causality in the flow of behavioristic, whose practice negates the uniqueness of each individual human being studied (individual differences). The generalist assumptions of knowledge based on objective and universal methods of natural sciences are at odds with the spirit of psychology harmonize humans. Therefore, the psychology of postmodernism comes as a critique and offer in understanding human behavior as a whole by using various paradigms both using communicative hermeneutics and Derrida deconstruction.